Comparações de comportamentos da Proteína C-reativa e da temperatura da pele dos membros inferiores de atletas profissionais de futebol em resposta a jogos consecutivos - Warley Henrique Duarte de Oliveira (2020)
Soccer involves high intensity, eccentric actions. These actions generate muscle damage that trigger inflammatory processes for tissue repair/remodeling. These inflammatory processes are characterized by overlapping phases and can be developed differently depending on the intervals between consecutive matches. Monitoring consecutive matches through physiological variables such as C-reactive protein (CRP) and skin temperature (Tsk) of the lower limbs (LL) can increase the understanding of the demand imposed on athletes and the temporal returno of homeostasis. Additionally, relativized analysis for high levels of these variables would contribute to the understanding of athletes' inflammatory responses between consecutive matches. The aim of the study was to compare the PCR and Tp behaviors of the lower limbs of professional soccer athletes from 3 consecutive games, in relation to Pre-match results (Baseline) and to compare the relative responses of these variables in 24, 48 and 72 hours after the 3 consecutive matches. The sample consisted of 12 professional soccer athletes (26.31 ± 4.45 years). Blood samples were taken to CRP analysis, and the Tsk of the LL was assessed through of Infrared Thermography. These evaluations took place in before 3 consecutive matches (Baseline), and every 24 hours after the matches. The monitoring of the total distances of the matches was assessed through of GPS. The CRP concentrations, and the Tsk of the LL at 24 hours after all matches and at 48 hours after match 3 were significantly higher than Baseline (P ≤ 0.05). CRP’s relativized responses were significantly higher at 48 hours after the 3rd match, compared to similar moment of the 1st and 2nd matches, respectively (P < 0.05; d > 0.62 d > 2.0). Similar results at 48 hours after the 3rd match were verified for the relativized responses of the Tsk (P < 0.05; d > 2.0; d > 2.0). There was not significant difference for the total distance of the matches (P > 0.20). In 24 hours after all the matches there are significant increases in PCR and Tp of the lower limbs, however in 48 hours, only after match 3 there was a similar result for both variables. The relativized results of 48 hours after match 3, and the result of the total distance of the matches, indicate a probable, cumulative effect of the load of the 3 matches.